Recent Studies of (+)-3-Carene Transformations with the Retention of the Native Framework - Serghei Curlat (Chemistry Journal of Moldova: General, Industrial and Ecological Chemistry, 2019)

(untitled)
This review presents last decade and some past especially relevant studies in the field of (+)-3-carene synthetic transformations. This paper discusses exclusively the transformations of (+)-3-carene, proceeding with the retention of the native bicyclic carbon skeleton. The data concerning the features of epoxidation and oxidation reactions of (+)-3-carene, the synthesis of sulphur- and selenium-containing derivatives and their use in asymmetric synthesis are given. It also describes methods for producing amino derivatives of (+)-3-carene, substituted heterocycles based on it, reactions for the preparation of aziridines, azido-alcohols and azidoamines, as well as chiral phosphites as bidentate ligands.